2012
DOI: 10.5501/wjv.v1.i5.142
|View full text |Cite
|
Sign up to set email alerts
|

Infectious laryngotracheitis virus in chickens

Abstract: Infectious laryngotracheitis (ILT) is an important respiratory disease of chickens and annually causes significant economic losses in the poultry industry world-wide. ILT virus (ILTV) belongs to alphaherpesvirinae and the Gallid herpesvirus 1 species. The transmission of ILTV is via respiratory and ocular routes. Clinical and post-mortem signs of ILT can be separated into two forms according to its virulence. The characteristic of the severe form is bloody mucus in the trachea with high mortality. The mild for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 80 publications
1
74
1
1
Order By: Relevance
“…Gallid herpesvirus 1 (GaHV-1), also known as avian infectious laryngotracheitis virus (ILTV), which belongs to the family Herpesviridae in the subfamily Alphaherpesvirinae, continues to cause substantial economic losses to the poultry industry worldwide (15). Both in vitro and in vivo studies have shown that ILTV infection blocks apoptosis in infected cells, thereby prolonging the life span of infected cells and consequently facilitating viral replication (16,17).…”
Section: Abstract Alphaherpesviruses Virus-host Interactions Paracrmentioning
confidence: 99%
“…Gallid herpesvirus 1 (GaHV-1), also known as avian infectious laryngotracheitis virus (ILTV), which belongs to the family Herpesviridae in the subfamily Alphaherpesvirinae, continues to cause substantial economic losses to the poultry industry worldwide (15). Both in vitro and in vivo studies have shown that ILTV infection blocks apoptosis in infected cells, thereby prolonging the life span of infected cells and consequently facilitating viral replication (16,17).…”
Section: Abstract Alphaherpesviruses Virus-host Interactions Paracrmentioning
confidence: 99%
“…Infectious laryngotracheitis (ILT) is an acute respiratory disease of chickens caused by avian herpesviridae Alphaherpesvirinae gallid Herpes virus 1 that infects the upper respiratory tract and ocular organ of poultry (Garba et al, 2012) and characterized by respiratory depression, gasping, and expectoration of bloody exudates (Yukihiro et al, 1988) with high rates of morbidity and mortality up to 70% in acute form of the infection and the mild form includes depression, reduced egg production up to 30 percent and weight gain, conjunctivitis, swelling of the infraorbital sinuses (almond shaped eyes), and nasal discharge (Shan-Chia and Joseph, 2012). All ages of chickens are affected, but chickens older than 3 weeks are most susceptible to ILTV.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the poultry presented respiratory signs, in most of the farms the IBV was not isolated, demonstrating that these signs can be confused with other respiratory diseases such as Laryngotracheitis and Coryza. Thus the diagnosis is essential for the confirmation of IB (27).…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de las aves de corral presentado signos respiratorios, en la mayoría de las granjas del IBV no fue aislado, lo que demuestra que estos síntomas se pueden confundir con otras enfermedades respiratorias como la laringotraqueitis y coriza. Así, el diagnóstico es esencial para la confirmación de IB (27).…”
Section: Discussionunclassified